São Paulo’s Sacred Art Museum: History of a collection - Mascarenhas, Christian (Estudos Avançados, 2021)
This article presents elements of our Master’s research to understand the constitution of the collection of São Paulo’s Sacred Art Museum (MAS-SP) and investigates its importance, thus contributing to the historiographic and heritage preservation debate in the city of São Paulo. The history of the creation of this museum is deeply connected to the pioneering “institutional collection thrust” of sacred art promoted in Brazil by Dom Duarte Leopoldo e Silva, the first archbishop of São Paulo, in the early 20th century. Differing somewhat from the others articles in this publication, we will not deal here with the decoration of religious spaces; however, we will address the institutionalization and historical relations of an important part of the heritage that once belonged to these spaces.